Implementasi Metode Diskusi Brainstorming Dalam Menumbuhkan Keaktifan Siswa Pada Mata Pelajaran IPS Terpadu - Sutan Sanata Islam; Ulfi Andrian Sari (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
The education system in Indonesia has undergone many changes. These changes have been made because various attempts at renewal in education have progressed. This progress makes teachers or educators expected to find new methods and equipment that can provide enthusiasm for learning for all students. Several attempts have been made by the teacher to improve learning outcomes in social studies subjects, namely by holding group discussions, providing additional varied practice questions, and repeating material that students have not yet understood. This study aims to: Know the Implementation of Brainstorming in Growing Student Activeness in Social Studies Subjects. This study uses a qualitative approach with descriptive methods. Data collection techniques include observation, interviews, and documentation. Data analysis refers to Miles, Huberman, and Saldana which consists of data collection, data condensation, data presentation, and data verification. The results of this study are the implementation of the brainstorming type discussion method is carried out by dividing students into several discussion groups, then the teacher gives a discourse on problems to students regarding learning topics, students issue their ideas, opinions and the teacher accommodates them without changing these ideas, Teachers and students together evaluate the ideas that have been issued by students in the learning process takes place.